(untitled) (Superficies y Vacío, 2012)
Plasma polypyrrole was synthesized on stainless steel and Nitinol (Ni-Ti alloy) substrates in order to obtain polymer-metal compounds with high adhesion. The work has the objective to cover metal surfaces with polymers to reduce the contact of metallic surfaces with biological tissues in human body implants. The metal samples were subjected to RF glow discharges with water vapor and argon to clean, oxidize and erode before the polymer coatings. After that, the synthesis of polymers was carried out by glow discharges during 10 min at 13.56 MHz, 10-1 mbar and 20 W. The results showed that the coating is carried out in consecutive thin layers with the morphology of the metal at the interface. The coated samples were immersed in phosphate solutions (PBS) pH = 7.4 to simulate the conditions of salt concentration in human arteries and veins. The PPy coated metal substrates have rough morphology with resistance to PBS solutions. However, Nitinol samples needed Ar besides water discharges to clean, oxidize and erode.